Usulan Standar Tingkat Pencapaian Perkembangan Anak (STPPA) Pendidikan Anak Usia Dini Usia 2-3 Tahun - Nanik Rahayu; Noor Padilah; Saniyya Putri Hendrayana; Reni Rulita; Debie Susanti; Nor Annisa (LP. Ma'arif Janggan Magetan, 2023)
This article discusses the process of growth and development of children aged 2-3 years which is continuous throughout the stages of life, but the speed of growth varies according to the stages of age. In the development of children aged 2-3 years. To achieve development, children need to achieve it in accordance with the standards of the child's level of achievement: religious-moral, physical-motoric, cognitive, linguistic, social-emotional, and artistic, language and art. This article aims to describe the development of abilities of children aged 2-3 years from various aspects of developmental achievement. Development is the increase in abilities or skills in more complex body structures and functions in a regular and predictable pattern as a result of experience and the process of movement, intellectual, social and emotional maturation. Development is influenced by heredity, environment, culture and family values in each individual. The combination of these factors gives rise to the wide variety of variations that can be observed in children. Growth and development occur very rapidly, therefore stimulation of children at this age is very important because healthy and intelligent children will grow and develop optimally. The rate of growth and development of children aged 2-3 years which is described in various sources and guidelines in the national curriculum, there are proposed indicators of development in aspects of religious-moral, physical-motoric, cognitive, linguistic, social-emotional, and artistic. The method used for data collection is in the form of library research, which is a method that can study various reference books and the results of previous similar studies.